Aerodynamic Study of Chord Length Effect in Low Speed Wind Turbine Using 6 DoF CFD Method - Sabina Aisyah Susanto; Hangga Wicaksono; Hilmi Iman Firmansyah; Mukhammad Fakhruddin (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2023)
The dependencies on fossil energy as a basic energy source has many negative impacts, therefore alternative energy is needed to overcome the problem, one of which is the alternative green energy wind turbines. However, wind turbines in Indonesia are difficult to implement because the wind speed in Indonesia is low, which is around 4-8 m/s, therefore it is necessary to do research to improve the ability of wind turbines applied in Indonesia. The analysis method using the 6 DoF CFD method and the experimental carried out using the wind tunnel. The blade used in this study is a custom combination airfoil with the chord lengths of 0.1 m, 0.15 m and 0.2 m. The results shows that, at wind speed of 8 m/s the blade with a chord length of 0.2 m has the greatest pressure of 47 Pa and rotational speed per minute of 76.1 rpm, this variation can be applied to low rpm generators. Whereas blades with a chord length of 0.1 m and a twist angle of 15o have a pressure of 47 Pa, and rotational speed of 97.24 rpm per minute, this variation can be applied to high rpm generators.